New serological platform for detecting antibodies against Mycobacterium tuberculosis complex in European badgers. Issue 1 (18th January 2019) - Infantes‐Lorenzo, Jose A.; Dave, Dipesh; Moreno, Immaculada; Anderson, Paul; Lesellier, Sandrine; Gormley, Eamonn; Dominguez, Lucas; Balseiro, Ana; Gortázar, Christian; Dominguez, Mercedes; Salguero, Francisco J.
Abstract: European badgers ( Meles meles ) have been identified as wildlife reservoirs for Mycobacterium bovis in the UK and Ireland, and may also have a role in the epidemiology of animal tuberculosis in other European regions. Thus, detection of M. bovis ‐infected badgers may be required for the purposes of surveillance and monitoring of disease levels in infected populations. Current serological assays to detect M. bovis infection in live badgers, while rapid and inexpensive, show limited diagnostic sensitivity. Here we describe and evaluate new ELISA platforms for the recognition of the P22 multiprotein complex derived from the purified protein derivative (PPD) of M. bovis . The recognition of IgG against P22 multiprotein complex derived from PPD‐B was tested by ELISA in the serum of badgers from the UK, Ireland and Spain. TB infection in the badgers was indicated by the presence of M. bovis in tissues by culture and histology at post‐mortem examination and TB‐free status was established by repeated negativity in the interferon γ release assay (IGRA). In experimentally infected badgers, humoral antibody responses against P22 developed within 45 days post‐infection. The ELISA tests showed estimated sensitivity levels of 74–82% in experimentally and naturally infected badgers with specificities ranging from 75% to 100% depending on the badger population tested. The P22 multi‐antigen based ELISAs provide a sensitive and specific test platform for improved tuberculosis surveillance in badgers. Abstract : Two new ELISA platforms were evaluated for recognition of the P22 multiprotein complex derived from the purified protein derivative (PPD) of M. bovis . Their estimated sensitivity levels of 74–82% in experimentally and naturally infected badgers with specificities ranging from 75% to 100%.